Agricultura familiar e agrotóxicos: desenvolvimento, transformações capitalistas e percepções de agricultores no interior do Ceará - Vieira, Mykaelly Morais (2021)
Family farming is a strategic category in the contemporary economic, social and environmental composition. Its scope is perceived worldwide, with around 500 million family farms that integrate the economy (IBGE, 2019). Economic, social and environmental transformations have given new meaning to this work, in the proportion that it has expanded dialogues and some similarities with agribusiness devices. Pesticides are a mediator between some trends in large-scale agriculture, with family farming. Faced with this device, a series of conflicts and clashes, in the socio-environmental axis (RIGOTTO, 2013, 2015, 2018), presents pesticides as a reality of risk to health. This investigation aims to understand how family farming has been reframed from the dynamics of agricultural work, with the use of pesticides, focusing on the perceptions of farmers / family members. The analytical field of this investigation is the rural community of Garapa I and the 24 de Abril settlement, which belong to the municipality of Acarape, located in the Massif de Baturité, located 61.8 km from Fortaleza in Ceará. We seek to enter the universe of farmers / family members as interlocutors of research, focusing our investigative look on their way of understanding / experiencing and building their work dynamics given the capitalist transformations. Specifically, we delineate the senses and meanings that pesticides assume in this work dynamic of the research agents. In this sense, our epistemological and theoretical-methodological positioning starts from praxis (MARX, 2011; FREIRE, 1987) together with the comprehensive analysis of social reality (WEBER, 1998). We moved the category of praxis to understand the work and the context of capitalist transformations within the scope of Brazilian family farming, its history and modernization, in the face of agribusiness (WANDERLEY, 2001; MAZOYER; ROUDART, 2010; MENDONÇA 2002; ABRAMOVAY, 1997). In this direction, we highlight the conflicts and socio-environmental implications of the use of pesticides in Brazil, and the possibility of transformation through agroecology (ALEXANDRE, 2009; CARNEIRO; et. Al. 2015; ABREU, 2016; LOPES, 2018). The approach allowed us to conclude that the senses and meanings that lead farmers to use pesticides are based on the daily needs emerging in the practice of working in the field. The farmers' work, coupled with their expectation of fruits due to the effort employed in the activity, are determining factors for the decision to use pesticides, in view of the ease of acquisition of the substances and the immediacy contained in the process of preparation and use in the fields. However, the principles of agroecology are fruitful and present possible paths in the construction of a socially conscious agriculture.